THE TEACHER AS A SUBJECT OF TREATMENT - Yu Sadikov (Galaxy International Interdisciplinary Research Journal, 2021)
The success of a teacher’s interactions with children depends in many ways on his or her pedagogical ability and pedagogical etiquette. In psychology, pedagogical skills are understood to mean certain psychological characteristics of a person. These qualities are a prerequisite for her to achieve high results in teaching and educating children as a teacher.